EFFECT OF ANTICONVULSANT DRUGS ON MONOVALENT CATIONS - Shafique, M.; Ashraf, M.; Shah, S.H.; Ghani, M.U. (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT: Sixty patients receiving anticonvulsant drugs like tegretol 9 Carbamazepine and 61 agematched controls were studied to determine the disturbances in sodium and potassium. levels There was a significant difference in sodium level the mean serum sodium levels of the subjects (138.8± 0.6 mEq/L) and the controls (141.7± 0.4 mEq/L). Thirteen (21.7%) of the subjects, but none of the controls, had sodium levels 135 mEq/L. But the mean values of potassium (4.3 ± 0.02 mEq/L), were not significantly changed as compared to controls. The risk of hyponatremia increased with age (subjects 30 years old had four limes the prevalence of hyponatremia as those < 30 years old.